The interaction of gender and declension in Germanic languages - Kürschner, Sebastian; Nübling, Damaris (Folia Linguistica, 2011)
In the Germanic languages, gender and declension are two classification systems with a restricted functional load. Still, both persist in many languages, and in  some of these languages they are even intimately interrelated, i.e. gender can be  predicted based on declension, or declension can be predicted based on gender. Several Germanic languages and dialectal varieties of German are compared with respect to this link between gender and declension. Based on contrastive data, the interaction seems to depend on the level of complexity, i.e. the number of declensions and genders. When complexity decreases, the conditioning of both categorization systems is either more strongly interrelated (leading to parallelization in the most extreme cases), or gender and declension are dissociated and bound to new, more transparent conditioning factors. The developments are interpreted against the background of the hypothesis that gender and declension are used complementarily in profiling the number category: gender profiles the singular, whereas declension profiles the plural.
Keywords: declension; gender; Germanic languages; German; inflectional morphology